Effects of (−)Epicatechin on the Pathology of APP/PS1 Transgenic Mice - Zeng, Yue-Qin; Wang, Yan-Jiang; Zhou, Xin-Fu (Frontiers in Neurology, 2014)
Background: Alzheimer’s disease is a multifactorial disorder characterized by the progressive deterioration of neuronal networks. The clearance of Aβ from the brain and anti-inflammation are potential important strategies to prevent and treat disease. In a previous study, we demonstrated the grape seed extract (GSE) could reduce brain Aβ burden and microglia activation，but which polyphenol plays a major role in these events is not known. Here we tested pharmacological effects of (-)epicatechin, one principle polyphenol compound in GSE, on transgenic AD mice. Methods: APP/PS1 transgenic mice were fed with (-)epicatechin diet(40mg/kg/d) and curcumin diet (47mg/kg/d) at 3 months of age for 9 months, the function of liver, Aβ levels in the brain and serum, AD-type neuropathology, plasma levels of inflammatory cytokines were measured. Results: Towards the end of the experiment we found long-term feeding of (-) epicatechin diet was well tolerated without fatality, changes in food consumption, body weight or liver function. (-)Epicatechin significantly reduced total Aβ in brain and serum by 39% and 40%, respectively, compared with control diet. Microgliosis and astrocytosis in the brain of Alzheimer’s mice were also reduced by 38% and 35%, respectively. The (-)epicatechin diet did not alter learning and memory behaviors in AD mice. Conclusions: This study has provided evidence on the beneficial role of (-)epicatechin in ameliorating amyloid-induced AD-like pathology in AD mice, but the impact of (-)epicatechin on tau pathology is not clear, also the mechanism needs further research.